2010
DOI: 10.1074/mcp.m900267-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoproteome of the Minimal Bacterium Mycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae belongs to the Mollicutes, the group of organisms with the smallest genomes that are capable of host-independent life. These bacteria show little regulation in gene expression, suggesting an important role for the control of protein activities. We have studied protein phosphorylation in M. pneumoniae to identify phosphorylated proteins. Two-dimensional gel electrophoresis and mass spectrometry allowed the detection of 63 phosphorylated proteins, many of them enzymes of central carbon meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 65 publications
3
44
0
Order By: Relevance
“…Phosphoproteome analyses revealed that numerous PTS components become phosphorylated at Ser or Thr residues, including the general PTS proteins EI and HPr as well as many sugar-specific PTS components (211)(212)(213)(214)(215)(216)(217). In firmicutes, HPr was found to be phosphorylated not only at Ser-46 but also at position 12, which can be Ser or Thr (212,213).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoproteome analyses revealed that numerous PTS components become phosphorylated at Ser or Thr residues, including the general PTS proteins EI and HPr as well as many sugar-specific PTS components (211)(212)(213)(214)(215)(216)(217). In firmicutes, HPr was found to be phosphorylated not only at Ser-46 but also at position 12, which can be Ser or Thr (212,213).…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, the B. subtilis glmM gene was deleted by transforming GP1365 with chromosomal DNA of B. subtilis GP588. In the latter strain, the chromosomal copy of glmM is deleted, and glmM is provided ectopically from a plasmid (33). The loss of the B. subtilis glmM gene was verified by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, if proteins are dephosphorylated by a specific phosphatase, then the expectation, in the absence of the phosphatase, is no change in the phosphorylation levels or increased levels of phosphorylation of proteins. In fact, the proteins identified in PrpC mutant of M. pneumoniae [49] behave in this manner. The differentially phosphorylated proteins identified in this mutant included RopE, an adhesion related protein P41, HMW3, MPN256 and MPN474.…”
Section: Resultsmentioning
confidence: 99%